Stewardship actions for device associated infections: An intervention study in the emergency intensive care unit - Rehab H. El-Sokkary; Essamedin M. Negm; Howaydah A. Othman; Mohamed M. Tawfeek; Wafaa S. Metwally (Elsevier, 2020)
Improving the practices of antimicrobial use in hospitals, especially in developing countries, is a challenging duty. Objectives: The aim of the study was to determine the effect of certain stewardship actions on the use of antibiotics for device-associated infections in the emergency intensive care unit in Egypt. Mehods: The intervention included establishment of AS team, design an antibiogram and preparation of antibiotic use guidelines, education, and infection prevention and control measures. Pre- and postinterventions surveys tookplace including: antibiotic prescription compliance, antibiotic cost, bacterial profile and antibiotic resistance rates. Results: Antibiotic prescription compliance improved, especially for prophylactic antibiotics prescription; in preintervention phase, 27.4% of cases received unindicated antibiotic prophylaxis vs 5.8% after intervention. A statistically significant decrease in cost after the intervention was reported (p = 0.04). Acinetobacter baumannii and Klebsiella pneumonia were the most frequently isolated pathogens (25.6%) and (21.8%) in pre and post-intervention phases respectively. A statistically significant decrease in the prevalence of MDR (X² = 11.9, p = 0.009) was observed. The most prevalent XDR is K-pneumonia (45% vs 17%) in phase 1&3. No pan drug-resistant isolates were detected. Conclusion: Sound antibiotic guidelines coupled with effective infection control precautions and education would be a good intervention, particularly with a leadership commitment.The use of microbiology tests to direct prescribing decisions should be a underscored. Sustained research initiatives may support the proper implementation of AS programmes in limited resource settings.